Personalism in orthodox theology - Gennadii Khrystokin (Cхід, 2016)
The paper looks into the personalistic doctrine of the orthodox theological tradition. It covers the prerequisites of development of Christian understanding of personhood in Judaism and Greek philosophy and analyzes the origin of the personalistic theory in the theological tradition of eastern patristics. The role of personalism in triadological and Christological concepts of the epoch of Oecumenical Councils is defined. The specifics of understanding of personhood in contemporary orthodox theological thought is explored. The author comes to conclusion that personalism of traditional orthodox theology is to large extent metaphysical because its content was created as a result of synthesis of evangelic world outlook and platonism whereas its language was borrowed from Aristotle's 'Categories". Personalism of contemporary orthodox thought adds existentialism to Christian world outlook in the 20th century. The above is confirmed through reviewing such works as P. Florensky's 'The Pillar and Ground of the Truth', V. Losky's 'The Mystical Theology of the Eastern Church' and John Zizioulas's 'Being and Communion. Studies in personhood and the Church' as well as 'Communion and otherness. Further studies in personhood and the Church'. In the 21st century personalism in Orthodoxy is enriched with personalistic phenomenology of emotional experience. The above is demonstrated by such conceptual works as C. Yannaras's 'Postmodern Metaphysics' and J. Manoussakis's 'God after Metaphysics'. In the opinion of the paper's author, recourse of contemporary orthodox theological thought to philosophy in handling Christian personalism is necessary not only for the purposes of apologetics but also for implementation of personalism as a system.